Characteristics of the Molecular Epidemiology of CTX-M-Producing Escherichia coli Isolated from a Tertiary Hospital in Daejeon, Korea - Kim, Semi; Sung, Ji Youn; Cho, Hye Hyun; Kwon, Kye Chul; Koo, Sun Hoe (Journal of microbiology and biotechnology, 2016)
The aims of this study were to characterize the molecular epidemiological profiles of CTX-M-producing uropathogenic Escherichia coli isolates from a tertiary hospital in Daejeon, Korea, and to investigate the genetic diversity and compare the prevalence of sequence types (STs) in different areas. Extended spectrum β-lactamase-producing E. coli strains isolated from urine were analyzed for CTX-M, integrons, and insertion sequence common regions (ISCRs) by PCR and sequencing. Multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), phylogenetic analysis, and rep-PCR were also used for molecular typing of the isolates. Of 80 CTX-M producers, 31 and 46 expressed CTX-M-15 and CTX-M-14, respectively. MLST analysis indicated that the most prevalent ST was ST131 (n = 34, 42.5%), followed by ST38 (n = 22, 27.5%), ST405 (n = 8, 10.0%), and ST69 (n = 6, 7.5%). Most CTX-M producers harbored class 1 integrons. ST131 strains belonged to phylogenetic group B2 and showed identical rep-PCR patterns, whereas ST69, ST38, and ST405 strains belonged to phylogenetic group D; the ST38 and ST405 strains displayed the same rep-PCR pattern, respectively. ST131 and ST38 isolates showed 21 and 19 distinct types, respectively, by PFGE. In Daejeon, D-ST38 CTX-M-14 producers were relatively more prevalent than in other countries and Korean cities. Our results indicate that CTX-M-producing E. coli isolates belonged mostly to ST131 or ST38 and were more related to hospital-onset than to community-onset infections and that the blaCTX-M gene may vary according to the ST.